Makna Lingkungan Hidup di Masa Sriwijaya: Analisis Isi pada Prasasti Talang Tuwo - Yenrizal Yenrizal (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
The purpose of this study is to understand the interpretation of the environmental aspects during the Sriwijaya kingdom in the 7th century. The interpretation is based on text written on the script of the Prasasti Talang Tuwo (Talang Tuwo inscription), the one and only inscription talking about the environmental arrangement. This study deploys a discourse analysis by Mangineau which discusses the discourse from three aspects: content, process, and emergence. Data are analyzed by qualitative method using environmental communication perspective. This study indicates that (a) the social situation in Sriwijaya’s era had determined the environmental interpretation; (b) the process occurred shows social context playing significant role, and (c) it shows how this process was taking place in certain stages.